ANALISIS KINERJA BIROKRASI DINAS TENAGA KERJA, TRANSMIGRASI, DAN KEPENDUDUKAN PROVINSI JAWA TENGAH - Widowati, Nina (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
Bureaucratic Performance in Indonesia until now goes as expected in the reform of the bureaucracy. It is commonly found diversion due to less optimal organizational machinery in carrying out their duties. Transmigration, Labor and Population Department of Central Java is an institution that can provide information to the public, especially on jobs, as well as workforce training. Unfortunately society is not optimizing services provided by that agency.